(untitled) (CIPEEX, 2026)
Introduction: Systemic arterial hypertension (SAH) is one of the main causes of morbidity and mortality in Brazil and worldwide, requiring special attention from Primary Health Care (PHC), which plays an essential role in its prevention and management. Objective: This literature review aims to assess the level of knowledge of PHC professionals regarding the prevention and management of SAH. Methodology: The methodology involved searching for scientific articles in the SciELO, LILACS, and PubMed databases, using the descriptors “arterial hypertension,” “primary care,” and “knowledge,” with a time frame limited to the last 10 years. Fourteen studies that met the inclusion criteria were selected. Results: The results indicate that, although health professionals demonstrate basic knowledge about the diagnosis and treatment of SAH, there are still significant gaps regarding adherence to clinical guidelines, multiprofessional approaches, and patient-focused health education. Care is often limited to the use of medication, with less emphasis on preventive actions and lifestyle changes. Furthermore, the lack of continuous training and updated protocols undermines the effectiveness of the care provided. Conclusion: It is concluded that there is a need to invest in the continuous training of PHC health teams, as well as in strengthening public policies that encourage educational practices, systematic patient follow-up, and interdisciplinary work. Expanding the technical-scientific knowledge of professionals is essential for the effective control of SAH, contributing to the reduction of complications and improvement in the quality of life of health system users.